2020
DOI: 10.18632/aging.202181
|View full text |Cite
|
Sign up to set email alerts
|

TRIM3 attenuates apoptosis in Parkinson's disease via activating PI3K/AKT signal pathway

Abstract: This article aims to study tripartite motif-containing protein 3 (TRIM3) effects on Parkinson's disease (PD). TRIM3 expression in venous blood of PD patients was detected by qRT-PCR. PD mouse model and PD SH-SY5Y cell model were constructed. PD cells were treated by LY294002 (a PI3K inhibitor). The apoptosis of PD mouse midbrain was detected. Glutathione (GSH) and superoxide dismutase (SOD) level in PD cells and mice midbrain was analyzed. Intracellular reactive oxygen species (ROS) and MMP were detected. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Apoptosis has been implicated as the mechanism of dopaminergic neuronal loss in Parkinson disease, as illustrated by the identification of apoptotic cells and DNA fragmentation in the substantia nigra of Parkinson diseased patients in post‐mortem and in vitro and in vivo studies (Balakrishnan et al, 2021; Erekat, 2018a; Ma et al, 2018; Teng et al, 2020). In addition to that, overexpression of active caspase‐8, ‐9, and ‐3, as well as increased levels of pro‐apoptotic proteins, such as BAX, and reduced anti‐apoptotic Bcl‐2 levels in the dopaminergic neurons of Parkinson disease in post‐mortem and in vitro studies confirmed the role of apoptosis in the pathogenesis of Parkinson disease (Balakrishnan et al, 2021; Bose & Beal, 2016; Dong et al, 2020; Ma et al, 2018; Moujalled et al, 2021).…”
Section: Apoptosis In Neurodegenerative Diseasesmentioning
confidence: 84%
“…Apoptosis has been implicated as the mechanism of dopaminergic neuronal loss in Parkinson disease, as illustrated by the identification of apoptotic cells and DNA fragmentation in the substantia nigra of Parkinson diseased patients in post‐mortem and in vitro and in vivo studies (Balakrishnan et al, 2021; Erekat, 2018a; Ma et al, 2018; Teng et al, 2020). In addition to that, overexpression of active caspase‐8, ‐9, and ‐3, as well as increased levels of pro‐apoptotic proteins, such as BAX, and reduced anti‐apoptotic Bcl‐2 levels in the dopaminergic neurons of Parkinson disease in post‐mortem and in vitro studies confirmed the role of apoptosis in the pathogenesis of Parkinson disease (Balakrishnan et al, 2021; Bose & Beal, 2016; Dong et al, 2020; Ma et al, 2018; Moujalled et al, 2021).…”
Section: Apoptosis In Neurodegenerative Diseasesmentioning
confidence: 84%
“…The PI3K/Akt signaling pathway plays an important role in neuronal cell proliferation, differentiation, and growth regulation and is considered crucial for regulating neuroinflammation and DA neuron loss. , Activation of the PI3K/Akt signaling pathway could lead to phosphorylation of Akt cascade, which is involved in inhibiting oxidative damage and thereby mediating the neuroprotection against PD . Here, Western blotting was applied to quantify the protein levels of PI3K and Akt as well as the levels of p-PI3K and p-Akt.…”
Section: Results and Discussionmentioning
confidence: 99%
“…61,62 Activation of the PI3K/Akt signaling pathway could lead to phosphorylation of Akt cascade, which is involved in inhibiting oxidative damage and thereby mediating the neuroprotection against PD. 63 Here, Western blotting was applied to quantify the protein levels of PI3K and Akt as well as the levels of p-PI3K and p-Akt. The decreased levels of p-PI3K and p-Akt were observed in MPTP-lesioned mice, while the ZIF-8@PB-QCT + NIR group demonstrated high levels in both p-PI3K and p-Akt (Figure 7J).…”
Section: Resultsmentioning
confidence: 99%
“…dili is associated with inappropriate activation of apoptotic cell death pathways (33)(34)(35)(36). apoptosis serves a key role in progression of liver disease, such as cirrhosis (37,38). apoptosis is mediated by two central pathways, the intrinsic and extrinsic pathway.…”
Section: Discussionmentioning
confidence: 99%